Sabellaria and Lygdamis (Polychaeta: Sabellariidae) from reefs off northeastern Brazil including a new species of Sabellaria - Santos, André Souza Dos; Brasil, Ana Claudia Dos Santos; Christoffersen, Martin Lindsey (Zootaxa, 2014)
Members of the polychaete taxon Sabellariidae Johnston, 1865 are known to live in sand tubes cemented onto rocky substrata, mollusk shells, or sea grasses. Of 37 known Sabellaria species, only nine were reported for the Brazilian coast, in all cases being associated with aggregates of other species. The genus is considered cosmopolitan. Herein we describe for the first time an aggregate of sabellariids composed by Sabellaria nanella and Sabellaria wilsoni. In addition, we describe a new species of Sabellaria. Lygdamis are represented by solitary species. None of the 17 known species were previously reported from the southwestern Atlantic Ocean. We report Lygdamis rayrobertsi for the first time in the South Atlantic.